A educação como transgressão: nos horizontes da escolarização de hansenianos no Pará do século XX a (re) criação da experiência de si - COSTA, Ghislaine Dias da (Universidade Federal do Pará, 2013)
To present Thesis that interferes in the group of researches developed by Pesquisa Education's Line: Curriculum, Epistemologia and History of the Program of Masters degree in Education of the Federal University of Pará, the 20TH century. Takes as corpus of study the narratives of five education ex-Hansenianos memories, documents and historical sources to analyze by triad power-know-subject, that experience as a transgressor. The theoretical research depart of contributions from authors transiting by post-structuralism, especially the thought of Michel Foucault where search-if a dialogue about parallel lives, education, subjectivation, transgression and aestheticization. The survey analyses show that the experience of schooling not only presents some specifics about the modes and the context in which it was carried, but, also, as for the singular and existential meaning that acquired for the hansenianos patients that entered the school in their lives, and with this they opened banks to experience both of transgressors processes itself as in the collective social life of the colony by decreasing the strength of subjectivation: make it possible to think that the Transgression in the field of education, plays an important role in Education to enable the creation of passages, gaps for new configurations of senses, new modes of existence, as a space for the recognition of the multiplicity of existence, the difference in the formation of subjectivities resistant, transgressive, creators; reveal a unique experience of schooling can contribute to re questioning knowledge and educational practice ethics and politically committed to the differences and contribute to redeem certain images sometimes forgotten history, the lives of infamous men, denied, silenced voices in contexts of schooling; Finally point to the prospect of teaching ethics and aesthetically oriented, capable of acts of creation and the transgression.